Bleeding duodenal ulcer in a patient with Hemophilia A: A case report - Baloska, Ivana; Lichoska Josifovikj, Fana; Baloski, Marjan; Trajkova, Sanja (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2024)
Hemophilia A is a hereditary bleeding disorder characterized by excessive musculocutaneous hemorrhage due to a congenital deficiency of factor VIII. While upper gastrointestinal bleeding in patients with hemophilia A has been reported globally, specific literature on this topic remains scarce, emphasizing the need for further research. Case presentation: A 38-year-old male presented at the Univesrity Clinic of Gastroenterhogepatology, reporting a recent episode of black stool three days prior to admission. His digital rectal examination was unremarkable, and levels of blood urea and nitrogen (BUN) were within normal ranges. Apart from Helicobacter pylori infection, the patient lacked significant risk factors for duodenal ulcers. An esophagogastroduodenoscopy (EGD) revealed a duodenal ulcer (classified as Forest Ib), and endoscopic hemostasis was performed using 9ml adrenaline solution. Coagulation factor VIII was administered prior to the procedure. Following the EGD, the patient was treated according to the duodenal ulcer protocol and hospitalized at the University Clinic. Conclusion: Recognizing risk factors, such as Helicobacter pylori infection and the use of nonsteroidal anti-inflammatory drugs, is crucial in managing duodenal bleeding ulcers in patients with Hemophilia A. Screening for Helicobacter pylori infection can significantly reduce the risk of ulcer-related bleeding episodes and enhance overall patient health. Further research and the development of clinical strategies are essential to optimize the management of duodenal ulcers in this patient population.